2019
DOI: 10.3390/socsci8010020
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting among Labor Union Representatives: Its Impact on Work Engagement and Job Satisfaction

Abstract: Labor Union activity still lacks recognition as an ordinary work activity. However, on the one hand, labor union representatives must deal with many tasks (internal and external) that can sometimes be overwhelming. On the other hand, given its vocational nature and the possibility that it offers for the workers themselves to organize their work, the area of trade unionism can be interesting for the study of job crafting and other phenomena associated with well-being, such as burnout or work engagement. Unfortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
1
18
0
3
Order By: Relevance
“…Firstly, the results obtained reveal the inexistence of a direct relationship between either type of job crafting and job satisfaction. Villajos et al (2019) also found that not all dimensions of job crafting predicted job satisfaction. In the model studied the predictive power was weak, explaining only 27% of the variance observed in job satisfaction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Firstly, the results obtained reveal the inexistence of a direct relationship between either type of job crafting and job satisfaction. Villajos et al (2019) also found that not all dimensions of job crafting predicted job satisfaction. In the model studied the predictive power was weak, explaining only 27% of the variance observed in job satisfaction.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have linked the components of job crafting with engagement and satisfaction. Villajos, García-Ael, and Topa (2019) found that those dimensions linked to an increase in structural and social resources and challenging demands were associated with engagement. However, only increased structural and social resources were found to be related to job satisfaction.…”
Section: Job Crafting Engagement and Job Satisfactionmentioning
confidence: 95%
“…Job performance was measured by the 7-item In-Role Behavior Scale (IRB) developed by Williams and Anderson [42]. The original version in English has been already used in the Spanish language in a previous study [43]. A sample item is: “fulfills responsibilities specified in the job description”.…”
Section: Methodsmentioning
confidence: 99%
“…Work performance was assessed using 7 items from the In-Role Behavior scale (IRB) of Williams and Anderson [37]. The original English version, which had already been translated into Spanish in previous studies [38], was adapted to the teaching collective for the present study. Examples of the items are: "I adequately complete the tasks assigned to me in the educational center where I work", "I fulfill the specific responsibilities of my teaching work", or "I am involved in activities that are going to be taken directly into account in the evaluation of my job performance (such as participation in educational, innovation or lifelong learning projects)".…”
Section: Instrumentsmentioning
confidence: 99%